A novel framework to transfer credits of computing courses on the basis of knowledge units in higher education institutions - Khan, Muhammad Asif; Almulhim, Abdelrahman Abdelaziz; Alkati, Safiullah Salem; Altarafi, Nasser Ehsan (Edelweiss Applied Science and Technology, 2025)
It is common practice for students that they transfer their study program from current department, college or institution to another entity. During transfer of a program students wish to transfer credits of their completed courses to other institution. It is important that the knowledge and skills obtained from a transferring institution meet the standards of the receiving institution. Sometimes it is difficult to map the courses in two different institutions due to vague course descriptions and learning outcomes; as a result, the course credits evaluators either approve or deny credit transfer request. In both situations students face difficulties coping with higher level course. Traditionally, it is suggested to find out the course outlines and learning outcomes of a course and then equalize the course. This traditional process does not give due course credits to students as learning outcomes or outlines of a course may be different among institutions. In this study, descriptive methodology employed quantitative approach to collect data through a simple questionnaire from university students. We have presented a framework which will help higher education institutions to determine equivalence credit hours of computing courses based on knowledge units of a program rather than course learning outcomes. The framework is validated by the data obtained by conducting interviews with university students which affirm the usefulness of the model to both students and institutions.